Platelet anti-aggregating activity of furosemide (Revista Española de Fisiología, 1976)
The effect of furosemide on platelet aggregation, factor 3 availability, and response to hypotonic stress has been studied. Furosemide greatly inhibits platelet aggregation, with ADP, epinephrine, collagen, ristocetin, thrombin and serotonin. The use of heparin as anticoagulant does not alter this effect. Furosemide action is not conducted through calcium chelation. Platelet factor 3 availability is not modified by furosemide. There is a direct correlation between furosemide concentration and inhibition in the second phase of platelet response to hypotonic stress. The possibility of a disorder furosemide induced on the platelet metabolism, is suggested.